Impact of daily bathing with chlorhexidine gluconate on ventilator associated pneumonia in intensive care units: a meta-analysis - Chen, Wensen; Cao, Quan; Li, Songqin; Li, Huifen; Zhang, Weihong (Journal of Thoracic Disease, 2015)
Objective: Ventilator associated pneumonia (VAP) is the most important nosocomial infection in intensive care units (ICUs). Our objective was to assess whether daily bathing with chlorhexidine gluconate (CHG) would significantly result in the reduction of VAP. Materials and methods: Meta-analysis of randomized controlled trials (RCTs) and quasi-experimental studies were conducted. The setting are medical, surgical, trauma, and combined medical-surgical ICUs. The patients are adult. We searched electronic search engine (PubMed), Embase and the Cochrane Central Register database for all published studies related to the application of daily CHG bathing with VAP risk. Results: In all, six articles reporting a total of 27,638 ventilator-days met the inclusion criteria; 132 patients in the CHG arm developed a VAP (13,349 ventilator-days), compared with 188 patients in the control arm (14,289 ventilator-days). Daily bathing with CHG was significantly associated with decreased incidence risk of VAP [relative risk (RR): 0.73, 95% confidence interval (CI): 0.57-0.92, I2=0%]. In the subgroup analysis, we found that daily bathing with 2% CHG impregnated cloths or wipes would reduce the incidence risk of VAP among before-and-after studies (pooled RR: 0.73, 95% CI: 0.57-0.93). Conclusions: The application of daily bathing with CHG would decrease incidence risk of VAP, which would be an important complementary intervention to barrier precautions.